Implementation of Parking Retribution Policy: Increasing Original Regional Income in Baolan District, Tolitoli Regency - Ayu Lestari; Andi Nur’aini; Daniati Hi Arsyad (Faculty of Social Science, Universitas Negeri Semarang, 2023)
This research aims to implement the parking retribution policy to increase Regional Original Income in the Susumbolan Market, Baolan District, and Tolitoli Regency, which still needs improvement. The problem is due to the need for more facilities for parking attendants, such as vests usually used in parking attendants, ID cards, whistles, and hats. This research aims to know how to implement a parking retribution policy to increase local revenue (PAD) in the Susumbolan market. This study used the descriptive qualitative method. The informants in this study were eight people, namely UPTD Pasar Susumbolan, the Market Coordinator, the Parking Attendant, and the people of the Baolan District. Data collection techniques in this study used observation, interviews, and documentation. The research results regarding the Implementation of Parking Retribution Policies in Increasing Regional Original Income (PAD) in the Susumbolan Market, Baolan District, and Tolitoli Regency using the theory of policy implementation proposed by 0045 Edward III have not run optimally. 1. communication went well; in the implementation of the parking, levy briefings were carried out almost every Monday so that the parking attendants understood their responsibilities. 2. Human resources are adequate but still inadequate from the dimensions of facility resources. Because parking attendants lack parking facilities such as vests, whistles, and ID cards, this refers to the payment for parking services. 3. The bureaucratic structure has been running well because it has standard operating procedures SOPs such as technical instructions on the process flow and work procedures for implementing parking retribution policies. 4. The disposition and attitude of the parking attendants have supported the implementation of the parking retribution policy in the supplementary market. It can be seen from the parking attendants who have carried out all stages in implementing the Parking Retribution Policy, such as pursuing the annual targets determined by the region and serving the community well.